Expressão de proteína antiviral de lonomia obliqua em sistema baculovírus/célula de inseto - Carmo, Ana Carolina Viegas (2012)
In recent years, the technology animal cells culture has allowed the development of many byproducts, especially those with pharmacological interest. Some of these products, the recombinant proteins, can be produced by heterologous expression systems on a commercial scale. Bacteria, yeast, mammalian cells and insects are some of the hosts used in these processes. As source of proteins with farmacological interest, the catterpillar Lonomia obliqua hemolinph was demonstrated to be a helpful organismo. Antiviral, antiapoptotic, antimicrobial and inducing growth proteins, are some of examples. Since the control of viral infections is a major interest to public health, the searching for new antiviral drugs has utmost importance. Several studies have reported the presence of active principles in the arthropods hemolymph. Recently, we demonstrated the existence of an antiviral protein in the hemolymph of the caterpillar Lonomia obliqua. This purified protein induced viral production reduction (TCID50 mL-1) over 157 times in cells infected with the measles virus, 61 times for polio and 61 times for influenza virus H1N1 infections. Thus, the present goals were building and expression of a recombinant plasmid contained coding sequences for expression of viral proteins (using baculovirus) in insect cell Sf-9 system. By this process, it was aimed to test biological activity of the protein. Further sequence analyses of this protein were performed using bioinformatics tools. The RNA of L. obliqua was extracted with Trizol reagent. RNA product was used in RT-PCR reactions with primers specific for the antiviral protein, based on the sequence of the cDNA libraries of L. obliqua tegument and spines, using all possible frame of translation for each cDNA. Restriction sites were inserted in cDNA sequence to insert it in pFastBacTM1 donor vector (Invitrogen). The sequence contained in selected clone of Escherichia coli DH5α was used for transformation into E. coli DH10Bac to obtain a bacmid by transposition process. This bacmid was used for antiviral recombinant protein expression in Sf-9 cells. This recombinant protein activity was tested in Picorna (EMC enchephalomiocardite), Rubeola and Herpes virus. In these trials, it was observed a replication reduction of 10,000, 10,000 and 1,000000 times, respectively. The bioinformatics analysis demonstrated that this protein is secreted, globular and probably belongs to a new class of proteins.